2013
DOI: 10.1007/s11743-013-1520-y
|View full text |Cite
|
Sign up to set email alerts
|

Achieving the Best Yield in Glycolipid Biosurfactant Preparation by Selecting the Proper Carbon/Nitrogen Ratio

Abstract: Pseudomonas aeruginosa RS29, the native biosurfactant‐producing strain isolated from the oil fields of Assam, India was used to investigate the influence of the carbon nitrogen ratio on production of the biosurfactant. The biosurfactant producing ability of the strain was measured based on surface tension (ST) reduction of the culture medium and the emulsification (E24) index. Production was greatly influenced by the sources of nitrogen and carbon as well as the carbon to nitrogen (C/N) ratio. Sodium nitrate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…Primarily, the amounts of the produced microbial surfactants depend on to the producer organism and factors like carbon and nitrogen sources, trace elements, and production conditions ( Patel and Desai, 1997 ). In the literature, there are studies focusing rhamnolipid production using different carbon sources ( Soberon-Chavez et al , 2005 ; Da Silva et al , 2009 ; Amani et al , 2013 ; Rikalovic et al , 2013 ; Saikia et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Primarily, the amounts of the produced microbial surfactants depend on to the producer organism and factors like carbon and nitrogen sources, trace elements, and production conditions ( Patel and Desai, 1997 ). In the literature, there are studies focusing rhamnolipid production using different carbon sources ( Soberon-Chavez et al , 2005 ; Da Silva et al , 2009 ; Amani et al , 2013 ; Rikalovic et al , 2013 ; Saikia et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is one of the physicochemical parameters that most influences lipopeptide production (Inès and Dhouha, 2015). In this study, we found that the optimal temperature for surfactin production by B. velezensis H2O-1 is about 30 C, i.e., a temperature commonly used for the production of surfactin by B. subtilis (Fisher and Sonenshein, 1991;Saikia et al, 2014).…”
Section: Effect Of Nitrogen Source and Culture Conditions On Surfactimentioning
confidence: 81%
“…The concentrations of these enzymes depend directly on the concentration of ammonia present in the culture medium. If nitrate is used as the sole source of nitrogen, it must first be reduced to ammonia and then enter the glutamate‐glutamine pathway (Saikia et al, ). Therefore, nitrate assimilation is slower, leading to low cell growth and, in the case of NaNO 3 , low surfactin production.…”
Section: Resultsmentioning
confidence: 99%
“…Various reports have been published in recent past years on the cost reduction of glycolipid production via the substitution of high-cost medium ingredients by complex agro-industrial wastes. Many renewable resources such as agro-industrial waste, hydrocarbon wastes and vegetable oils have been used as the sole source of carbon for biosurfactant wileyonlinelibrary.com/jsfa 112,113 Cristallization Sophorolipid 96,114 production either by solid state fermentation or submerged fermentation. Several bacterial, 76,81,82 yeast, 25,83 fungal 84 and actinobacteria 11,60 strains were screened as glycolipid biosurfactant producers.…”
Section: Valorization Of Food Byproducts and Agro-industrial Wastes Bmentioning
confidence: 99%